Bankim Chandra Chattopadhyay : an intellectual biography - Sen, Amiya P., 1952- (New Delhi : Oxford University Press, 2008)
Biography of a 19th century Bengali author.
"Chronological list of major literary works": p. [123]-[131].
Keywords: Chatterji, Bankim Chandra, -- 1838-1894.; Authors, Bengali -- 19th century -- Biography